A cyclic correlation-based time domain channel estimation scheme - Khan, A.M. (Institute of Electrical and Electronics Engineers Inc., 2017)
In the presence of guard band sub-carriers, the existing correlation-based time-domain channel estimation schemes do not perform well and suffer from high computational complexity. Herein, we proposed an optimized time domain channel estimation scheme with high accuracy and low complexity. In proposed correlation error cancellation (CEC) solution, the larger part of actual channel estimation solution is estimated from no-guard band (without null sub-carriers) solution, which can be easily obtained by choosing appropriate pilot design. In order to estimate the complete actual solution, the correction term can be obtained from the difference in the actual transmitted pilot and the pilot used for no-guard-band solution. The theoretical analysis and simulation results show that the proposed CEC solution reduces the complexity up to 0(L2) in one-step of iteration and achieves accuracy close to Cramer Rao Bound (CRB). © 2016 IEEE.